PENGARUH E-WOM DAN TALENT COMMUNICATOR FEMALE DAILY DUDES TERHADAP BRAND IMAGE - ELVIRA MAHARANI; Anindita Lintangdesi (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2021)
The advent of the internet and social media connected audiences to the digital age. This advanced technology helps audiences to get information without the boundaries of space and frequency. There is one way to make communication through the internet with electronic word of mouth through social media which will be conveyed through a talent communicator , namely Female Daily Dudes, who can create a brand image for every audience who gets the information. The purpose of this study was to determine the effect of electronic word of mouth on brand image, the influence of talent communicator on brand image, and the influence of electronic word of mouth and talent communicator of FD Dudes on brand image. This research method uses a quantitative approach, uses multiple linear regression analysis techniques and data collection is carried out by distributing questionnaires to 100 samples of Female Daily Network subscribers for one month in October 2020. The results are: 1) electronic word of mouth can have a significant positive effect on brand image; 2) talent communicator has a significant positive effect on brand image; 3) electronic word of mouth and talent communicator have a significant positive effect on brand image.